2012
DOI: 10.1186/2045-5380-2-15
|View full text |Cite
|
Sign up to set email alerts
|

Increased ratio of anti-apoptotic to pro-apoptotic Bcl2 gene-family members in lithium-responders one month after treatment initiation

Abstract: BackgroundLithium is considered by many as the gold standard medication in the management of bipolar disorder (BD). However, the clinical response to lithium is heterogeneous, and the molecular basis for this difference in response is unknown. In the present study, we sought to determine how the peripheral blood gene expression profiles of patients with bipolar disorder (BD) changed over time following intitiation of treatment with lithium, and whether differences in those profiles over time were related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 40 publications
3
33
0
Order By: Relevance
“…42 Also deserving mention was BCL2L13, an apoptosis facilitator 43 (from the Bcl-2 family of apoptosis mediators) upregulated in BD. Interestingly, a shift in expression from pro-to anti-apoptotic Bcl-2 genes has been reported in lithium-responsive BD patients after treatment, 44 supporting a role for apoptosis in BD pathophysiology (although changes in BCL2L13 itself were not significant in that study). The upregulation of immune genes, detected also in the functional pathway analysis and later in the co-expression analysis (via the M7 module), echoes a similar trend from transcriptomic studies of BD (and schizophrenia) investigating other brain regions and blood.…”
Section: Discussionsupporting
confidence: 48%
“…42 Also deserving mention was BCL2L13, an apoptosis facilitator 43 (from the Bcl-2 family of apoptosis mediators) upregulated in BD. Interestingly, a shift in expression from pro-to anti-apoptotic Bcl-2 genes has been reported in lithium-responsive BD patients after treatment, 44 supporting a role for apoptosis in BD pathophysiology (although changes in BCL2L13 itself were not significant in that study). The upregulation of immune genes, detected also in the functional pathway analysis and later in the co-expression analysis (via the M7 module), echoes a similar trend from transcriptomic studies of BD (and schizophrenia) investigating other brain regions and blood.…”
Section: Discussionsupporting
confidence: 48%
“…In addition, the role of lithium in the modulation of cell death and apoptosis has been previously suggested by several studies (Bielecka and Obuchowicz, 2008; Breen et al, 2016; Chiu and Chuang, 2010), although the role of specific genes in this mechanism still needs to be unraveled. Top signaling pathways that were suggested to underlie the anti-apoptotic properties of lithium include the modulation of the Wnt pathway (Hu et al, 2011), mitochondrial function and calcium homeostasis (Alda, 2015; Scola et al, 2014), the expression of anti-apoptotic proteins (Dwivedi and Zhang, 2014; Lowthert et al, 2012), neurotrophic factors (Dwivedi and Zhang, 2014; Emamghoreishi et al, 2015a; Hellweg et al, 2002), among others (Alda, 2015; Bielecka and Obuchowicz, 2008). Accordingly, a recent study has shown that lithium upregulates a gene module specific to apoptosis signaling and exert regulatory effects on apoptosis-controlling proteins involved in mitochondrial and endoplasmic reticulum function in LCLs from BD patients (Breen et al, 2016), which corroborates our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Beech et al [16] conducted studies of gene expression changes in peripheral lymphocytes in bipolar subjects on lithium treatment for 1 month as well as bipolar subjects prospectively treated with lithium for 6 months [17]. After 6 months of treatment, responders had a greater upregulation of antiapoptotic genes (BCL2) while proapoptotic genes were downregulated.…”
Section: Introductionmentioning
confidence: 99%